Sistem Infomasi Pelayanan Kependudukan di Kantor Lurah Sioldengan Kecamatan Rantau Selatan berbasis Web - Siregar, Mulia Rahmat (Journal of Computer Science and Information System(JCoInS), 2022)
Resident events are changes in address, move / come to settle, stay limited, and change the status of living people to permanent residence. Important events such as birth, death, marriage, divorce, appointment, ratification of children and changes in citizenship status experienced by a person is an incident that must be reported because of the implications of changes in identity data or population papers. every important event requires valid evidence to be administered and recorded in accordance with the provisions of the law. recording and processing population data is the responsibility of the district / city government, which starts from the kelurahan office. The service needs to be done quickly and precisely to get an information. The method of data collection used is by observation (interview), interview (interview), and study literature. The programming used is web programming using MySQL and PHP databases. This study resulted in the design of web-based population service data processing applications in the office of Siurah Village with North Sumatra District. Hopefully this application can improve the performance process even better in processing population data with easier.